Morphological processing on sentence comprehension in Chinese : an EEG study on dyslexic children in Singapore - Ho, Glenn Yun Xin (2019)
Morphological awareness has arguably been taken as a salient construct of word reading in Chinese, which involves the ability to identify the order of morphemes presented in compound words and to distinguish meanings between homographs. To date, many behavioural studies have established impaired phonological processing as one of the most prominent features of dyslexia in English, but less research has looked into the relationship between morphological processing and dyslexia in Chinese from a cognitive perspective. Therefore, the current study adopted an electrophysiological approach to investigate if dyslexic children will display significantly different N400 responses from poor adult readers when processing various morphological information contained within the sentence-final two-character compound words that are presented in simplified Chinese across congruent, flipped and partial conditions in a sentence acceptability task. It was found that both adult participants and dyslexic children displayed a lack of N400 effects across all three conditions, which suggests a language proficiency related, rather than a dyslexia-specific deficit in morphological processing. In summary, the findings of the current study could potentially inform educators in the field about formulating targeted strategies for intervention that would contribute towards improving the overall quality of learning for dyslexic children. Future studies could look into comparing dyslexic children with reading-level matched non-dyslexic children for a more comprehensive view of the current research direction.